Review of medical physiology - Ganong, William F (New York ;;London : McGraw-Hill Medical, 2005)
Ideal for self-assessment and USMLE Step 1 review, this book provides a current and concise overview of mammalian and human physiology. Thoroughly revised and updated, examples from clinical medicine have been integrated throughout the chapters to illuminate important physiologic concepts. Features more than 700 illustrations and a self-study section with 630 multiple choice questions
Previous ed.: 2003
Includes bibliographical references and index
Keywords: Energy Metabolism -- Metabolism; Physiology -- Biochemistry